Clean Olympians? Doping and anti-doping: The views of talented young British athletes - Bloodworth, A.; McNamee, M. (International Journal of Drug Policy, 2010)
Background: Review articles suggest a small but significant proportion (between 3 and 12%) of male adolescents have used anabolic-androgenic steroids (AAS) at some point (Yesalis and Bahrke, 2000; Calfee and Fadale, 2006). In sport, the use of prohibited substances or processes to enhance performance, collectively referred to as `doping`, is banned by both sports` National and International Governing Bodies, and by the World Anti-Doping Agency (WADA) who run an extensive testing programme and educational initiatives designed to foster anti-doping attitudes.